Adaptation and learning processes of stroke survivors and family carers: a scoping review. (20th October 2021) - Moura, A; Castanheira Pais, S; Magalhães, P; Alves, E
Abstract: Background: Knowledge on the processes of adaptation and learning after stroke are scarce, hindering the development of evidence-based public health strategies to promote survivors and family carers' health and wellbeing, across the post stroke trajectory. This study aims to assess the available evidence on the processes of adaptation and learning after stroke, by mapping the main barriers and enablers according to the perspectives of stroke survivors and family carers. Methods: A scoping review was performed, following PRISMA-ScR guidelines. The electronic databases PubMed, ISI Web of Science, PsycINFO and SciELO were searched for empirical, peer-reviewed, original, and full-length studies on the processes of adaptation and learning of stroke survivors and family carers, in March 2021. Eligibility and data extraction were conducted by two independent researchers. The main qualitative data were explored by thematic content analysis and quantitative findings were synthesized. Results: The included studies, 29 qualitative and 1 quantitative, were published between 1994 and 2019. Most of the studies were carried out with small samples and without a specific focus on the adaptation and learning processes after stroke. Barriers and enablers to stroke adaptation and learning processes were influenced by physical, psychological and social characteristics. The poor physical and functional status of survivors, the inability to maintaining the Activities of Daily Living, emotional disturbances, lack of support and information, and changes in roles, were identify as main barriers to stroke adaptation. Using coping strategies and having psychological, educational, and financial support were described as enablers. Conclusions: Public health policies and practices should consider the physical, psychological and social barriers and enablers to the stroke adaptation and learning processes to ensure a high-quality long-term care centred on survivors and family carers. Key messages: Robust theoretical and methodological studies, specifically designed to deeply explore and describe the post stroke adaptation and learning processes, are needed. Understand the main barriers and enablers to adaptation and learning after stroke may be useful for developing health education interventions centred on survivors and carers preferences and needs.